Comparison of capsular stretching and passive joint mobilisation in idiopathic adhesive capsulitis of the shoulder; a randomised controlled trial - Maria Safdar; Tariq, Ramsha; Ayesha Bashir; Muhammad Affan Iqbal; Nadia Ishtiaq; Nimrah Kanwal (Journal of the Pakistan Medical Association, 2026)
Objective: To compare the effects of passive joint mobilisation versus capsular stretching on pain, range of motion and quality of life in patients with stage-II adhesive capsulitis of the shoulder joint. Method: The randomised control trial was conducted at Lady Reading Hospital and Khyber Teaching Hospital, Peshawar, Pakistan, from February to July 2023, and comprised patients aged 30-50 years diagnosed with idiopathic stage-II adhesive capsulitis of the shoulder joint. The patients were randomised into control group A and experimental group B. Group A was treated with Maitland mobilisation, while group B was treated with capsular stretching. The treatment lasted 12 sessions delivered 3 times a week for four weeks. Pre- and post-intervention assessment was done using a goniometer for shoulder range of motion, Numeric Pain Rating Scale for pain intensity, and the Shoulder Pain and Disability Index to measure disability associated with the affected joint. Data was analysed using SPSS 22. Results: Of the 38 participants mean age was 45.50 ± 4.14 years. Baseline values showed no significant differences between groups (p> 0.05). Both groups demonstrated significant intragroup improvements in shoulder flexion, extension, abduction, internal and external rotation, and SPADI scores following intervention (p <0.001). Post-intervention, the control group showed significantly greater improvements in flexion, extension, abduction, and SPADI scores (p<0.001), while internal rotation improved more in the experimental group (p=0.003). no significant intergroup difference was observed for external rotation (p=0.228). Significant time–group interaction effects were observed for flexion, extension, and SPADI, with the largest effect size for SPADI (n² = 0.605). Pain severity improved in both groups, with a shift from predominantly severe pain at baseline to mainly mild and moderate pain post intervention. Conclusion: Both interventions significantly improved shoulder range of motion and reduced pain and disability. However, greater improvements were observed in shoulder flexion, extension, abduction, and SPADI scores in the control group, while internal rotation improved more in the experimental group, with similar gains in external rotation. Randomised Controlled Trial No: NCT05903768 Keywords: Adhesive capsulitis, Range of motion, Shoulder pain and disability index, Numeric pain rating scale.